Foxtail Millet NF-Y Families: Genome-Wide Survey and Evolution Analyses Identified Two Functional Genes Important in Abiotic Stresses - Feng, Zhi-Juan; He, Guan-Hua; Zheng, Wei-Jun; Lu, Pan-Pan; Chen, Ming; Gong, Ya-Ming; Ma, You-Zhi; Xu, Zhao-Shi (Frontiers in Plant Science, 2015)
It was reported that Nuclear Factor Y (NF-Y) genes were involved in abiotic stress in plants. Foxtail millet (Setaria italica), an elite stress tolerant crop, provided an impetus for the investigation of the NF-Y families in abiotic responses. In the present study, a total of 39 NF-Y genes were identified in foxtail millet. Synteny analyses suggested that foxtail millet NF-Y genes had experienced rapid expansion and strong purifying selection during the process of plant evolution. De novo transcriptome assembly of foxtail millet revealed 11 drought up-regulated NF-Y genes. SiNF-YA1 and SiNF-YB8 were highly activated in leaves and/or roots by drought and salt stresses. Abscisic acid (ABA) and H2O2 played positive roles in the induction of SiNF-YA1 and SiNF-YB8 under stress treatments. Transient luciferase (LUC) expression assays revealed that SiNF-YA1 and SiNF-YB8 could activate the LUC gene driven by the tobacco (Nicotiana tobacam) NtERD10, NtLEA5, NtCAT, NtSOD or NtPOD promoter under normal or stress conditions. Overexpression of SiNF-YA1 enhanced drought and salt tolerance by activating stress-related genes NtERD10 and NtCAT1 and by maintaining relatively stable relative water content (RWC) and contents of chlorophyll, superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and malondialdehyde (MDA) in transgenic lines under stresses. SiNF-YB8 regulated expression of NtSOD, NtPOD, NtLEA5 and NtERD10 and conferred relatively high RWC and chlorophyll contents and low MDA content, resulting in drought and osmotic tolerance in transgenic lines under stresses. Therefore, SiNF-YA1 and SiNF-YB8 could activate stress-related genes and improve physiological traits, resulting in tolerance to abiotic stresses in plants. All these results will facilitate functional characterization of foxtail millet NF-Ys in future studies.